Effects of a branched-chain amino acid drink in mania. - Scarna, A; Gijsman, H; McTavish, S; Harmer, C; Cowen, P; Goodwin, G (2003)
BACKGROUND: Administration of a complex tyrosine-free amino acid drink acutely decreases manic symptoms. Although a nutrient-based approach to illness management is attractive, complex amino acid drinks are too unpalatable for repeated administration. AIMS: To assess whether a simple, branched-chain amino acid (BCAA) drink diminishes manic symptoms acutely and following repeated administration. METHOD: Twenty-five patients with mania were randomly and blindly allocated to treatment with BCAA (60 g) or placebo daily for 7 days. RESULTS: Relative to placebo, the BCAA drink lowered mania ratings acutely over the first 6 h of treatment. In protocol completers there was a persistent advantage to the BCAA group 1 week after the end of treatment. CONCLUSIONS: A nutritional intervention that decreases tyrosine availability to the brain acutely ameliorates manic symptoms. Further studies are required to assess whether this approach has longer-term efficacy.